2021
DOI: 10.3390/cells10030536
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor Is Essential for Larval Epithelial Apoptosis and Adult Epithelial Stem Cell Development but Not Adult Intestinal Morphogenesis during Xenopus tropicalis Metamorphosis

Abstract: Vertebrate postembryonic development is regulated by thyroid hormone (T3). Of particular interest is anuran metamorphosis, which offers several unique advantages for studying the role of T3 and its two nuclear receptor genes, TRα and TRβ, during postembryonic development. We have recently generated TR double knockout (TRDKO) Xenopus tropicalis animals and reported that TR is essential for the completion of metamorphosis. Furthermore, TRDKO tadpoles are stalled at the climax of metamorphosis before eventual dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…In the case of the normal mucosae of vil-TRa1/Apc mice, the molecular phenotype is even more intriguing, given that these portions of the intestines have histological appearance similar to that of the vil-TRa1, but show molecular features close to the tumors. According to the literature and also considering our work, THs-TRs definitively play a pivotal role in intestinal development and homeostasis in both mouse and amphibians by regulating the expression of a large panel of genes, including those belonging to the WNT pathway and cell cycle regulators (37,53,54). It is important to underline that all these studies provide data that can be now used in bioinformatics and statistics analyses for a direct comparison of TH-TR dependent mechanisms in the intestine of different species.…”
Section: Discussionmentioning
confidence: 75%
“…In the case of the normal mucosae of vil-TRa1/Apc mice, the molecular phenotype is even more intriguing, given that these portions of the intestines have histological appearance similar to that of the vil-TRa1, but show molecular features close to the tumors. According to the literature and also considering our work, THs-TRs definitively play a pivotal role in intestinal development and homeostasis in both mouse and amphibians by regulating the expression of a large panel of genes, including those belonging to the WNT pathway and cell cycle regulators (37,53,54). It is important to underline that all these studies provide data that can be now used in bioinformatics and statistics analyses for a direct comparison of TH-TR dependent mechanisms in the intestine of different species.…”
Section: Discussionmentioning
confidence: 75%
“…Wen L et al and Choi J et al reported that T 3 and TRα have indispensable roles during the intestinal remodeling of amphibian metamorphosis ( 25 , 26 ). Thra -/- and Thra -/- Thrb -/- (TR double knockout) mutations in Xenopus tropicalis were shown to result in reduced larval epithelial cell apoptosis and reduced adult stem cell formation/proliferation during metamorphosis ( 27 , 28 ). Similarly, cell proliferation in the crypt was found to be reduced in both Thra knockout mice and Pax8 -/- mice ( 19 , 20 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result supports the role of unliganded TR to avoid precocious metamorphosis for proper tadpole growth. Finally, removal of TR prevents the disappearance of tadpole-specific tissues (Shibata et al, 2020(Shibata et al, , 2021.…”
Section: Involvement Of Thyroid Hormonesmentioning
confidence: 99%